Pengaruh Tari Ayam Modifikasi Terhadap Perkembangan Motorik Kasar Anak di Taman Kanak-Kanak Jabal Rahmah Padang - Henifo Oktari; Serli Marlina (PG-PAUD Trunojoyo, 2019)
This research begins with the challenge of implementing gross motor development that has not supported coordinated body movement. This study aims to find out how to change the gross motoric skills of children in Jabal Rahmah Padang Kindergarten. This study uses quantitative compilation of Quasi Eksperiments. The study population was all children in Jabal Rahmah Padang Kindergarten, and the Purvosive Sampling sampling technique, namely classes B1 and B2 each of which could be contacted by 10 children. Thehtechniquehofhcollectinghdatahusinghahtesthconsists of 5 points of approval and a data collection tool using the approving sheet.hThenhthehdatahishprocessed by the difference test (t-test). Based on the data analysis, the average experimental class test is 85 and SD is 8.06 while the control class 77 and SD is 6,78 in the hypothesis testing obtained by tcount (2,279 and ttable  of 2,100 at the real level = 0,05 and dk = 18. It can be concluded that the use of modified chicken dance opposes the gross motor development of children in Jabal Rahmah Padang Kindergarten 2018/2019.